A Review of Chemical Composition and Bioactivity Studies of the Most Promising Species of Ganoderma spp. - Katarzyna Sułkowska-Ziaja; Monika Balik; Andrzej Szczepkowski; Monika Trepa; Gokhan Zengin; Katarzyna Kała; Bożena Muszyńska (Diversity, 2023)
This paper presents the current state of knowledge on the biological activity and possible medicinal applications of selected species of the genus Ganoderma: Ganoderma adspersum (Schulzer) Donk, Ganoderma applanatum (Pers.) Pat., Ganoderma carnosum Pat., Ganoderma lucidum (Curtis) P. Karst., Ganoderma pfeifferi Bres., Ganoderma resinaceum Boud. These inedible, wood-decaying fungi are pathogens that cause the enzymatic decomposition of wood. They are a valued natural medicinal resource and have been used in traditional Far Eastern medicine for centuries. Research conducted on these species using modern analytical methods has led to advances in knowledge of the potential therapeutic use of compounds isolated not only from basidiocarps but also from biomass obtained by in vitro methods. Recent pharmacological studies have confirmed the known traditional uses of these species, elucidated previously unknown mechanisms of biological action, and found evidence of new biological activities, such as anticancer, cytotoxic, antiallergic, and neuroprotective activities. Furthermore, the article updated the state of knowledge on the general mycological characteristics of these species.